The Training of Making Graphical User Interface (GUI) Using Python for Teachers and Students of Engineering Vocational School in Purwakarta - Diky Zakaria; Muhammad Husni Muttaqin; Galura Muhammad Suranegara; Elysa Nensy Irawan; Liptia Venica (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of this community service activity is to introduce the Python programming language to teachers and students of vocational school in Purwakarta exploiting an application to create a simple graphical user interface (GUI). Python is a programming language that is currently trending. The training was carried out in 3 stages, namely preparation, implementation and evaluation. As a result, participants were able to follow this training well and were able to create their own version of a simple GUI. Participants were also able to integrate their GUI with Arduino. After this activity, participants are expected to be able to explore how to make simple GUI using the modules that have been given.